2001
DOI: 10.1046/j.1523-1747.2001.01298.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Multiple Cytochrome P450 Enzymes and Multidrug Resistance-Associated Transport Proteins in Human Skin Keratinocytes

Abstract: Cytochrome P450 enzymes metabolize various endogenous and exogenous small molecular weight compounds. Transport-associated proteins, such as P-glycoprotein, multidrug resistance-associated protein and lung resistance protein are overexpressed in drug-resistant cell lines, as well as in human tumors from various histologic origins, including malignant melanoma. Little is known about the expression and function of cytochrome enzymes and multidrug resistance-associated transport proteins in human skin; therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
212
6
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(230 citation statements)
references
References 41 publications
7
212
6
5
Order By: Relevance
“…Early studies demonstrating the ability of animal skin to metabolize benzo[a]pyrene suggested expression of CYP1A1 in skin. Indeed, CYP1A1 mRNA has been found in all human skin sources probed to date, although data supporting expression of CYP1A1 protein is limited to KCs (Baron et al, 2001;Saeki et al, 2002;Yengi et al, 2003). In contrast, studies probing for CYP1A2 mRNA have found that message for expression of this gene in skin or skin cells is undetectable (Baron et al, 2001;Saeki et al, 2002).…”
Section: Evidence For the Expression Of Drug-metabolizing Enzymes In mentioning
confidence: 99%
“…Early studies demonstrating the ability of animal skin to metabolize benzo[a]pyrene suggested expression of CYP1A1 in skin. Indeed, CYP1A1 mRNA has been found in all human skin sources probed to date, although data supporting expression of CYP1A1 protein is limited to KCs (Baron et al, 2001;Saeki et al, 2002;Yengi et al, 2003). In contrast, studies probing for CYP1A2 mRNA have found that message for expression of this gene in skin or skin cells is undetectable (Baron et al, 2001;Saeki et al, 2002).…”
Section: Evidence For the Expression Of Drug-metabolizing Enzymes In mentioning
confidence: 99%
“…Although constitutive expression of xenobiotic-metabolizing enzymes has been detected in normal keratinocytes [2,3] the levels of drug-metabolizing enzymes are generally much lower in the skin than those in the liver and intestine [4][5][6][7]. Thus, skin permeability rather than drug metabolism appears to be the major barrier to topical bioavailability [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Xenobiotic transporters (ABCs and SLCs) have broad specificity and are involved in both uptake (influx) and secretion (efflux) of their substrates, thereby affecting their cellular disposition. Constitutive expression of multidrug-resistance associated proteins (MRP, ABCC) or solute carrier organic anion transporting polypeptides (OATPs) has been detected in human keratinocytes [2,3,10,11]. The expression of ABCB1 (multidrug resistance protein 1, P-glycoprotein or P-gp) has only been found after keratinocyte treatment with dexamethasone [2].…”
Section: Introductionmentioning
confidence: 99%
“…Some of them, in particular weak contact sensitizers, are transformed into highly reactive species. It has been shown that the epidermis possesses multiple cytochrome P450 (CYP) isoenzymes that are able to metabolize xenobiotics to these highly reactive species (Baron et al, 2001). these enzymes are present in keratinocytes, which are the main cells of the epidermis, but they also are present in antigen presenting cells such as monocytes or dendritic cells.…”
Section: Qualitative and Quantitative Allergen-specific Protein Profimentioning
confidence: 99%